Antimicrobial Substance Produced by Lactobacillus sp. TGR-2 Isolated From Growol - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Lactic acid bacteria strain TGR-2 was isolated from growol (fermented raw cassava) and then identified as Lactobacillus sp. TGR-2. According to results of the turbidimetric assay, the neutralized supernatant of LacÂ¬tobacillus sp. TGR-2 were able to inhibit the growth of spoilage and pathogenic bacteria, i.e., Staphylococcus aureus FNCC 0047, Salmonella iyphimurium FNCC 0050, Escherichia coli FNCC 0091, Bacillus cereus FNCC 0057, and Morganella morganii FNCC 0122. The antimicrobial activity of neutralized supernatant of Lactobacillus sp. TGR-2 was stable at room temperaÂ¬ture for 60 min, pH 3-8